Efektivitas Ekstrak Daun Maja (Crescentia Cujete L.) Sebagai Antibakteri Pada Bakteri E. coli dan S. aureus - Ningrum, Hastuti Tri Ratna; Hidayah, Dia Rohmatul; Larassati, Fitry; Wisanti, Wisanti (Universitas Sebelas Maret, 2019)
Maja leaves (Crescentia cujete L.) is one type of plant that has the potential to be antibacterial. The bioactive compounds in maja leaves that function for antibacterials are saponin and tannin. The purpose of this research was to determine the antibacterial effect of maja leaf extract on E. coli and S. aureus bacterial growth. The research method was used experimental research using the basic design of a completely randomized design (RAL) and the data were analyzed using a one-way Anava test. Based on the results of the test it was found that C. cujete L. leaf extract was the most effective for inhibiting the E. coli and S. aureus bacteria growth with 25% leaf extract concentration. The diameter of inhibition zone was formed 10,66 mm in E. coli and 12,33 mm in S. aureus.